INTEGRATION METHODS FOR TEACHING BIOPHYSICS IN HIGHER EDUCATION INSTITUTIONS (International Conference on Educational Discoveries and Humanities, 2025)
The article examines integration methods that contribute to the enhancement of educational and methodological support in the credit-module system (CMS). It analyzes contemporary approaches to integrating educational technologies, interdisciplinary connections, and digital tools to improve learning effectiveness.